Analysis of the Effectiveness and Contribution of Tax Collection with Warning Letters, Compulsory Letters, and Orders to Implement Confiscation Towards the Disbursement of Tax Arrests (Case Study at KPP Madya in the Kanwil DJP West Java I) - Khairani, Rizka; Priyono, Agus Puji; Herdianti, Selly (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
The purpose of this study is to determine how effective tax collection is and how much it contributes to the disbursement of tax arrears. This study uses a qualitative descriptive approach. The ratio data used in this study are the performance report of the collection section, tax revenue reports, and other research-related data. The data used in this study include primary data and secondary data. The effectiveness and contribution ratio are some of the tools used by researchers in descriptive ratio analysis. The results of this study indicate that the effectiveness of tax collection at KPP Madya Bandung and KPP Madya Dua Bandung in 2019-2023 is included in the ineffective category when viewed from the realization of the achievement of tax collection targets. Meanwhile, the level of contribution of tax collection actions to the disbursement of tax arrears is classified as less contributive. The implementation of tax collection procedures has many obstacles, including the response of Taxpayers who are less cooperative in tax collection actions. KPP Madya in the West Java I Regional Office of the Directorate General of Taxes in this case KPP Madya Bandung and KPP Madya Dua Bandung have prepared various strategies as an effort so that the disbursement of tax arrears can run smoothly.